ANALISIS PENGARUH PENGELUARAN PEMERINTAH DI BIDANG PENDIDIKAN, KESEHATAN DAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI KOTA PAREPARE - Ladung, Fajar (Economos : Jurnal Ekonomi dan Bisnis, 2018)
Analysis of the Effect of Government Expenditures in the Field, Education, Health and Infrastructure on the Economic Growth of the City of Parepare ", (Supervised by Baharuddin S and Muchtar Lamo). This study aims to determine government spending in the City of Parepare, South Sulawesi Province in the last 8 years and to find out the condition of regional spending from 2010-2017. This type of research is quantitative research. The object of this study is the Local Government of the City of Parepare, Data collection techniques using documentation to collect reports on the realization of government expenditure in 2010-2017 in the city of Parepare, and unstructured interviews to employees of the Parepare City Development Planning Agency. in the field of education and infrastructure affect the economic growth in the city of Parepare. (2) the influence of education on economic growth is 0.014 <0.05 and t table value of -4.218> 2.776 then the hypothesis is accepted. (3) health influence on economic growth is 0.512> 0.05 and t table value is -0.718 <2.776 then the hypothesis is rejected. This means that there is no significant influence between government spending in the health sector on Economic Growth. (4) has a value of t 2.976 with a significant probability value of 0.041 Significant t is smaller than ? (0.05), it is known that the value for the influence of Infrastructure on economic growth is 0.41 <0.05 and the t table value is -2.976> 2.776 The hypothesis is accepted .